Plan de desarrollo y ordenamiento territorial (PDOT) de la parroquia Quinara perteneciente al cantón Loja. - Ortíz Torres, Richard Guillermo (2011)
The Territorial Classification is that that leaves of the recognition for all its population, of the geographical and human possibilities that it contains, in a mark of respect to the atmosphere. To this respect they are positive the measures that are carrying out with the Plan of Development and Ordination of the Territory, elaborated, with the collaboration of several public institutions, where it is proven that the country should change the current pattern of occupation of the territory and to look for new development styles, thinking about alternative roads, environmentally conceived that drive at better levels of quality of life for the Ecuadorian population., recommending for it the creation of economic activities in the counties and parishes of the country making stress in the integral use of the environmental resources. The administration of the territories should always register in the mark of the National Plan for the Good one to Live, in the National Territorial Strategy and with base in the competitions that the Constitution assigns to the decentralized autonomous governments of the parochial level The Plans of Development and Parochial Territorial Classification, with foundation in the Cantonal Plans, they define an objective vision - toward where the parochial territory goes - the goals and strategies that should be applied to reach it; the form in that he/she should be organized the territory and the norms and dispositions that should complete the entities and the citizenship to use and to occupy the territory so that their sostenibilidad is guaranteed. Defining the actions likewise - you program and projects - that should be taken to end to reach the integral development that generates conditions of good to live for the citizenship. In this mark of the competitions settled down in the Constitution, the development plan and parochial territorial classification, it should be articulate with the plans of the cantonal and provincial levels, so that conditions of coherence, integral and complementary are believed